The Side Effect Of Applying Single Slot Substitution Drill Technique Through Flascard On Students Grammar Mastery - Rahawi, Rabika (Universitas Muhammadiyah Sumatera Utara, 2021)
This study was carried out to find out the students achievement in simple past tense using Single Slot Substitution Drills. The descriptive quantitative methods was applied to describe the data. The population of this research was the second class of SMP Negeri 3 Labuhan Deli Satu Atap , which was divided into the experimental and control class and the total of the sample was 51 students. The researcher gave 40 questions about simple past tense to collect the data in pre-test and post-test. T-test formula was used by the researcher to analyze the data. In this research, it was found that the mean of pre-test score in experimental class was 53.04 and in control class was found 47.29. Meanwhile, the mean of post-test score which found in experimental class was 77.93 and in control class was 76.58. It can be counted from the students score that tcount was 0.910, whereas the ttable was 0.329 for = 0.05 with the degree of freedom (df) 51. It means that tcount was higher than ttable (0.910 0.329) So, alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected in this research. In an addition to this result, using of Single Slot Substitution Drills had significant effect as media in English teaching learning process.